História e Memória do Teatro em Caxias do Sul (1982 - 2024) - Beltrami, Miguel (My University, 2024)
The present master's thesis proposes a study of some aspects of the existing theater companies in the city of Caxias do Sul, located in the state of Rio Grande do Sul - Brazil between 1982 and mid-2024. By analysing the vouchers of Pedro Parenti Municipal Theater, it was possible to identify the companies that remained active for longer and with the biggest number of stagings: Misturas e Bocas, Miseri Coloni, Oficina Um, T.E.R. (Aicnalubma, Plexus e Nexus), Atrás do Pano, Tem Gente Teatrando, Kaleidoscópio, Cena Livre, Mise-en-Scène, Quiquiprocó, Atores Reunidos, Casa das Marocas, Usina de Teatro, Teatro Mecânico, Ueba - Produtos Notáveis, Cia2 and A Gangorra. Consequently, these theater companies and their respective creators consist of the main narrative in this master's thesis. We briefly and unpretentiously comment on topics related to the main theme with the aim of contextualizing Caxias - theatrical moment: Pedro Parenti Municipal Theater, Bento Gonçalves Popular Theater Festival - FETEBE, Gaúcho Amateur Theater Festival, UCS Festival, Caxias em Cena, among other theater exhibitions and festivals, including those directed by the local theater companies themselves. As it consists of a recent and untold story with live witnesses, we employed oral history as the main methodology and used the works of authors Alessandro Portelli and Verena Alberti as references. Thus, members of the aforementioned companies were interviewed, the preference being given for their creators: Agostinho Basso, Clerí Ana Pelizza, Gabriel Zeni de Oliveira, Henriette Fossati Metsavaht Cará, Idalzi Stockmans, Jonas Marcel Piccoli, Jorge Antônio Valmini, Juarez Luis Barazetti, Justina Inês Andrighetti, Magali Helena de Quadros, Marcondes Ribeiro Tavares, Renato Luiz dos Santos, Roberto Carlos Ribeiro da Silva, Rubens Cesar Baretta, Vera Elenita Medeiros and Volnei Cunha Canônica. In different arrangements, I spoke with Andréa Peres Trindade Soares, Janio Pereira Nunes and José Valter de Oliveira. A diversity of sources helped to complement this research: newspaper periodicals, theater programs, data and provided information. Historians Durval Muniz de Albuquerque Júnior, Carlo Ginzburg, Michel Foucault, Marta Goveia de Oliveira Rovai and Daphne Patai sensibly weave together historiographical meanings. The author Jorge Dubatti makes the dialogue between history and theater. [resumo fornecido pelo autor]
Esta dissertação de mestrado propõe um estudo sobre alguns aspectos dos grupos de teatro da cidade de Caxias do Sul do estado do Rio Grande do Sul - Brasil entre os anos de 1982 a meados de 2024. Após analisar os borderôs do Teatro Municipal Pedro Parenti foram identificados os grupos que permaneceram mais tempo em atividade e com uma quantidade maior de montagens: Misturas e Bocas, Miseri Coloni, Oficina Um, T.E.R. (Aicnalubma, Plexus e Nexus), Atrás do Pano, Tem Gente Teatrando, Kaleidoscópio, Cena Livre, Mise-en-Scène, Quiquiprocó, Atores Reunidos, Casa das Marocas, Usina de Teatro, Teatro Mecânico, Ueba ? Produtos Notáveis, Cia2 e A Gangorra. Assim, esses grupos e seus idealizadores figuram como narrativas protagonistas nesta dissertação. De maneira despretensiosa e breve fala-se de temas correlatos ao tema principal com o intuito de contextualizar a cena teatral caxiense: Teatro Municipal Pedro Parenti, Festival de Teatro Popular de Bento Gonçalves - FETEBE, Festival Gaúcho de Teatro Amador, Festival da UCS, Caxias em Cena entre outras mostras e festivas de teatro, inclusive os que tiveram como realizadores os próprios grupos de teatro local. Uma vez que se trata de uma história ainda não contada e recente, com testemunhas vivas, foi utilizada como principal metodologia a história oral tendo como referências os autores Alessadro Portelli e Verena Alberti. Dessa maneira foram entrevistados representantes dos grupos citados, preferencialmente os seus idealizadores: Agostinho Basso, Clerí Ana Pelizza, Gabriel Zeni de Oliveira, Henriette Fossati Metsavaht Cará, Idalzi Stockmans, Jonas Marcel Piccoli, Jorge Antônio Valmini, Juarez Luis Barazetti, Justina Inês Andrighetti, Magali Helena de Quadros, Marcondes Ribeiro Tavares, Renato Luiz dos Santos, Roberto Carlos Ribeiro da Silva, Rubens Cesar Baretta, Vera Elenita Medeiros e Volnei Cunha Canônica. Em outros formatos conversei com Andréa Peres Trindade Soares, Janio Pereira Nunes e José Valter de Oliveira. Outras fontes diversas ajudam a complementar a pesquisa: periódicos jornalísticos, programas de espetáculos, dados e informações cedidas. A costurar sensivelmente os sentidos historiográficos o historiador Durval Muniz de Albuquerque Júnior, Carlo Ginzburg, Michel Foucault, Marta Goveia de Oliveira Rovai e Daphne Patai. Dialogando entre história e teatro o autor Jorge Dubatti. [resumo fornecido pelo autor]
Keywords: Teatro - Caxias do Sul (RS) - História; Teatro - Caxias do Sul (RS) - 1982-2024; História oral; Memória; Representação teatral; Theater - Caxias do Sul (Brazil) - History; Theater - Caxias do Sul (Brazil) - 1982-2024; Oral history; Memory; Acting